Survey of satisfaction with care in a rheumatology outpatient clinic. Issue 2 (February 1992) - Hill, J; Bird, H A; Hopkins, R; Lawton, C; Wright, V
Abstract : Consumer satisfaction is increasingly recognised by hospital administrators and health care providers as an important aspect of health care. A study was undertaken to investigate the satisfaction with care among patients with rheumatoid arthritis (RA) attending a rheumatology outpatient clinic at Leeds General Infirmary. The Leeds satisfaction questionnaire was developed and rigorously tested for reliability (Cronbachs alpha) and stability (test/retest). The Leeds satisfaction questionnaire was then completed by 70 patients with RA who had attended the Leeds General Infirmary on at least three previous occasions. The results showed that patients were, in general, satisfied with the care they received. The highest satisfaction scores were obtained on the scale for technical quality and competence of health professionals. The least satisfaction was accredited to the difficulty of unscheduled access to the clinic and the lack of continuity with the providers of care. The time spent in the waiting area before consultation was highlighted as the one aspect which caused the greatest dissatisfaction.